Empowering the Research Future of Medical Students: Reflections on the Third Edition of the IJMS World Conference of Medical Student Research (WCMSR), 2024 - Aljbour, Omar; Carrington, Chloe; Sebesi, Hanna; Bonilla-Escobar, Francisco J. (International Journal of Medical Students, 2025)
The third edition of the IJMS World Conference of Medical Student Research (WCMSR) highlighted the significance of fostering research opportunities for medical students worldwide. Held on October 26, 2024, the event featured 35 authors from 19 countries, presenting 40 abstracts through oral and video presentations. Accessible to a global audience via YouTube Live, the conference attracted over 1,000 viewers who engaged in discussions and voting. The event emphasized the importance of affordable, inclusive participation, offering students a platform to showcase their research, gain feedback from experts, and build professional networks. With a nominal fee, IJMS removed financial barriers to entry, ensuring equitable access for junior researchers. The conference continues to empower medical students to advance their research, academic, and clinical skills, fostering a global community dedicated to the future of medical science.